Cortical thickness and functional connectivity changes in Chinese chess experts - Ouellette, David J. (PLoS One, 2020)
BACKGROUND: Repeated practice to acquire expertise could result in the structural and functional changes in relevant brain circuits as a result of long-term potentiation, neurogenesis, glial genesis, and remodeling. PURPOSE: The goal of this study is to use surface-based morphology (SBM) to study cortical thickness differences in Chinese chess experts and novices, and to use regions of cortical thickness differences as seeds to guide a resting state connectivity analysis of the same population. METHODS: A raw public dataset from Huaxi MR Research Center consisting of 29 Chinese chess experts and 29 novices was used in this study, with both T1-weighted and resting state functional MRI. Surface based morphometry was performed on the T1 images with the Freesurfur pipeline, with a vertex significance threshold of p<0.05 and a cluster false discovery rate of α < 0.05. Regions with significant differences were used in a seed-based comparison of resting state functional connectivity carried out with Statistical Parameter Mapping (SPM) and the Connectivity Toolbox (CONN). Regions of connectivity differences within groups were computed with a voxel significance threshold of p<0.05 and a cluster false discovery rate of α < 0.01. RESULTS: Ten regions of the cortex of Chinese chess experts were found to be thinner than chess novices, including regions involved in visual processing, attention, working and episodic memory, and mental imagery, as well as several regions in the prefrontal cortex. There were no regions where experts’ cortices were thicker than novices. Three of the thinner regions exhibited increased functional connectivity to distant brain regions in chess experts. CONCLUSIONS: Brain regions that are structurally affected by chess training are associated with processes that would likely have a high utility in chess expertise. Using a hierarchical control model, we hypothesize that the functional changes linked with some of these structural changes are related to the professionally trained chess players’ ability to perceive and use contextual information, visuospatial perception, and outcome prediction in the domain of chess, all contributing to their exceptional performance.